DEVELOPMENT OF THE PENSION SYSTEM IN UZBEKASTAN (European Journal of Economics, Finance and Business Development, 2024)
The article analyzes the pension reform and the results of its development, which began in the years of independence, and draws conclusions based on the analysis. Social payments, allowances and pensions received by citizens from the state budget and non-budgetary funds are of great importance among citizens. Pensions are paid in full to working pensioners. In this article, we list these and other major changes that have taken place in the pension system in recent years.